(untitled) (Research, Society and Development, 2022)
Introduction: In the last decades the population has experienced nutritional, socioeconomic and habits epidemiological transformations with a consequent increase in associated diseases. Thus, these transitions that transform the daily life of the population, also change the nutritional profile of children. Objective: To identify a prevalence of weight, overweight and obesity in two to five year olds living in the municipality of Trindade in the state of Goiás. Methods: This is a descriptive epidemiological study that used the Food and Nutrition Surveillance System (SISVAN) as an online database, assessing the nutritional status of children aged between two and five years, considering the factors: weight x age and BMI x age in the years 2013 to 2021 quantity. Results: There was a reduction in the year of children beyond 2013, 2015 and 2020, apart20 there was an increase in the number of very low weight children in 2015, however, in general, Trindade presented in every year the largest municipality of children with high weight. Conclusion: There was a high percentage of overweight in children aged 2 to 5 years. In addition, through the data obtained, it is concluded that the municipality of Trindade presented a discrepancy in the amount of data to be included by SISVAN in each weight category compared to Brazil in 201. In this sense, the need to supply the network of epidemiological data as well as an intervention through public policies, aiming at an increase in the percentage of children who currently.